Introduction Of Advanced Pedagogical And Information And Communication Technologies Into The Educational Process In Teaching Japanese Hieroglyphs (Czech Journal of Multidisciplinary Innovations, 2023)
As globalization accelerates in all spheres of society, it is inevitable that the interest in learning foreign languages will grow at the level of demand. This creates the need to research effective methods of teaching foreign languages, including Japanese, and put them into practice. The article analyzes the experiences of several foreign scientists on the methodology of effective teaching of hieroglyphs